PERAN SISTEM INFORMASI AKUNTANSI BAGI USAHA MIKRO KECIL DAN MENENGAH PADA DINAS KOPERASI USAHA KECIL DAN MENENGAH KABUPATEN MANDAILING NATAL - Fadhilah Nondangari (Unitri Press, 2022)
Accounting has an important role for the progress of MSMEs in Mandailing Natal Regency. But now many employees at MSMEs in Mandailing Natal do not know how important accounting is for compiling company financial reports. The role of accounting information systems for MSMEs is very important to know the development of these MSMEs. This study aims to determine the role of accounting information systems for MSMEs in Mandailing Natal at the Office of Small and Medium Enterprises Cooperatives, Mandailing Natal District. The data collection techniques used in this study were based on observations made during the internship. The data analysis method used is descriptive analysis based on the MSME data obtained. The results of this study are that there are still data that are not in accordance with the existing business categories in MSMEs. Therefore, the role of accounting information systems is very influential on MSMEs in the Office of Small and Medium Enterprises Cooperatives, Mandailing Natal District.